Harmonic Reduction Using Shunt Active Filter for Electrical Installation. (February 2020) - Jamal, A; Putri, S G; Chamim, A N N; Syahputra, R
Abstract: This paper presents harmonic reduction using an active shunt filter for hospital building electrical installation. Generally, harmonic installation in electric power systems is caused by non-linear electrical loads, especially the ones containing coils, such as air conditioners, pump machines, fans, and others. It might cause excessive heat in a distribution transformer which supplies an electrical installation in a multi-story building. In this regard, the heat is a power loss and has the potential to shorten the life of a distribution transformer, and therefore, efforts are needed to reduce harmonics. The use of active filters is one of the most effective strategies for reducing harmonics. In this study, a shunt active filter application in the electrical installation of a hospital building was carried out. The results showed the filter reduced harmonic currents significantly, to the extent that the harmonic threshold was still under the IEEE standard.